Role of Manipur Chakra in polycystic ovarian syndrome- a case report - Dr. yasmeen khan; vinod choudhari (Ayurline: International Journal of Research in Indian Medicine, 2022)
ABSTRACT BACKGROUND Manipur chakra is a solar plexus situated in the abdominal vicinity and influences various abdominal organs to perform their functions like digestion and hormonal secretions. The present case focuses on the stimulation of the Manipura chakra through various yoga poses and beej mantra meditation which varies according to chakra. AIM To evaluate the effect of Manipur chakra stimulation in polycystic ovarian syndrome through yogasanas. MATERIAL AND METHODS A study of a 27-year-old female patient diagnosed with PCOS is made to perform the asanas influencing Manipur chakras and beej mantra meditation for 3 months every day for 45 minutes under the guidance of a yoga instructor. Ultrasonography of ovaries is done before and after the completion of 3 months. OBSERVATIONÂ The course leads to the withdrawal of periods after 3 months, and continuation of the process for 3 months leads to reversal of PCO symptoms and clear ovaries. CONCLUSION Yogic poses and pranayama that influence the pancreas governed by Manipur chakra have a significant role in changing the autonomic activity either sympathetic or parasympathetic.